DAMPAK MEDIA SOSIAL BAGI PERUBAHAN SOSIAL EKONOMI MASYARAKAT DI KABUPATEN PANDEGLANG - Arianto, Bambang (Journal of Digital Business and Innovation Management, 2022)
This article aims to elaborate on the impact of social media on socio-economic changes in citizenship. This is because the existence of social media has contributed to influencing the joints of civic life, especially in Pandeglang Regency. Moreover, the majority of citizens who come from various backgrounds use social media for various daily activities. The impact is that until now, there has been a fundamental change at the citizenship level due to the presence of social media. These socio-economic changes were created due to the adaptation of new habits to the presence of social media, resulting in new patterns in all aspects of social life. This study used a qualitative descriptive, explanatory method using in-depth interviews with residents who use social media in Pandeglang Regency. This study states that social media significantly affects socioeconomic changes in citizenship. These changes include changes in behaviour, mindset, communication, dealing with citizenship and creating a digital entrepreneurship ecosystem in Pandeglang Regency, Banten Province.